ANALISIS SISTEM PENGENDALIAN INTERNAL KAS PADA UMKM COFFEE SHOP UP TO YOU KANDANGAN - Yasir, Muhammad Yasir; Sutomo, Ibnu (Jurnal Ilmiah Ekonomi Bisnis, 2024)
This research aims to determine the process of the internal control system which is integral to the actions and activities carried out continuously by the leadership and all employees to provide adequate confidence in achieving organizational goals at the MSME Coffee Shop UP TO YOU. The method used is descriptive qualitative. The results of this research show that the components of a good internal control system have not yet been fully met, because there are still deficiencies in controlling the recording of financial reports in terms of incoming financial transactions, and they have not yet fulfilled good internal control in the area of organizational structure relating to the appropriate division of tasks. responsibility for the position assigned. To overcome this, UP TO YOU MSME leaders must create routine or regular monitoring and evaluation of internal cash.